Alternative Energy Sources - Wasiak, Andrzej L. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The search for alternative sources of energy is an attempt to solve two of the main problems facing the modern world. Today's resources are mainly based on fossil flammable substances such as coal, oil, and natural gas. The first problem is related to the expected and observed depletion of deposits, not only those available but also less accessible. Another is related to global warming from emissions of greenhouse gases (mainly carbon dioxide) as well as emissions of other pollutants in the atmosphere. Mitigating the harmful effects of fossil fuel use is an obvious challenge for mankind. This Special Issue includes articles on the search for new raw materials and new technologies for obtaining energy, such as those existing in nature, methane hydrates, biomass, etc., new more efficient technologies for generating electricity, as well as analyses of the possibilities and conditions of use of these resources for practical applications.